The Early Arab Historians’ Approaches to the Biography of Khalid Ibn Al-Walid: A Comparative Critical Study: مناهج المؤرخين العرب المتقدمين في تناول سيرة خالد بن الوليد رضي الله عنه: دراسة مقارنة - Ali Hamad Mohamed Aljneibi, Fatima; Mohd Nor, Mohd Roslan; Abdul Hamid , Faisal @ Ahmad Faisal (Journal Al-Muqaddimah, 2025)
This article examines the methodologies employed by prominent early Arab historians in studying the biography of the Companion Khalid ibn al-Walid (may Allah be pleased with him), focusing on methodological differences and their impact on shaping his historical image. Ibn Ishaq adopted a narrative approach, collecting multiple reports and presenting them in a sequential storytelling format, which imparted an epic dimension to his biography. Al-Waqidi provided extensive accounts of Khalid’s military campaigns, relying on weak chains of transmission that later drew methodological criticism. Ibn Sa’d combined the approaches of hadith scholars and maghazi (military campaign) historians, offering a well-documented and balanced account without resolving contradictions among differing reports. Al-Tabari employed a historical methodology that collected multiple chains of narration and presented them impartially, making his work a significant reference for understanding Khalid’s military and political role. Al-Baladhuri focused on the administrative aspects of Khalid’s conquests, portraying him as a political leader balancing sword and diplomacy, while Ibn Abd al-Barr included Khalid’s biography within his encyclopedic compendium of the Companions, adhering to comprehensiveness and moderation. This methodological diversity resulted in multiple historical portrayals of Khalid, underscoring the necessity of a comparative critical approach that balances reliable narration with objective analysis, free from legendary embellishment or sectarian bias, thereby presenting a comprehensive, multi-dimensional image in Islamic historiography.